The State of Florida v. Kelvin Lee Coleman Jr.: the implications of neuroscience in the courtroom through a case study - Loizidou, Panagiota (Psychology, crime & law, 2023)
Neuroscience can provide evidence in some cases of legal matters, despite its tenuous nature. Among others, arguing for diminished capacity, insanity, or pleading for mitigation is the most frequent use of neurological evidence in the courtroom. While there is a plethora of studies discussing the moral and legal matters of the practice, there is a lack of studies examining specific cases and the subsequent applications of brain knowledge. This study details the capital punishment trial of Kelvin Lee Coleman Jr., charged in 2013 with double murder in Tampa, Florida, to illustrate the extent that expert opinions – based on neuroimaging, neurological, and neuropsychiatric examinations – had an impact on the court’s decisions. The defendant was sentenced to life imprisonment without the possibility of parole. According to the comments of the trial’s jury, the most influential reason for not sentencing the defendant to death is the fact that during the incident was that he was under extreme mental and emotional disturbance. Other reasons were evidence of brain abnormalities resulting from neurological insult, fetal alcohol syndrome, and orbitofrontal syndrome contributing to severely abnormal behavior and lack of impulse control.